Controlled Access and Availability: A Conundrum in Academic Libraries - Hyland, Anne Maureen (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
In response to the University of Calgary librarians' concerns regarding access policies for atypical items the relevant literature was examined and Canadian universities surveyed. Operating within the specific university context and the general principle of maximization of access and availability, guiding principles and specific criteria were developed for four categories of atypical items. En réponse à l’inquiétude des bibliothécaires de l’Université de Calgary au sujet des politiques d’accès des items atypiques, la littérature pertinente a été examinée et les universités canadiennes ont été étudiées. Opérant à l’intérieur du contexte universitaire spécifique et du principe général de maximisation de l’accès et de la disponibilité, des principes directeurs et des critères spécifiques ont été développés pour quatre catégories d’items atypiques.